COMPARISON OF DRYING SHRINKAGE AND DRYING CREEP KINETICS IN CONCRETE - Lenka Dohnalová; Petr Havlásek (Acta Polytechnica CTU Proceedings)
The aim of this paper is to show and compare the time evolution of drying shrinkage and drying creep in concrete from three different perspectives. The first one analyzes the basic equations defined in the most common design codes and prediction models for the description of the long-term behavior of concrete (ACI 209, EC2, Model Code 2010, B3, B4). Next, the evolution of drying creep and shrinkage is examined by processing suitable experimental data available from the database developed at the Northwestern University. Finally, the last point of view investigates the results obtained from the finite element simulations employing the material point approach, in particular, the material model based on the Microprestress-Solidification theory.